Increased peripheral blood TCD4(+) counts and serum SP-D levels in patients with chronic paracoccidioidomycosis, during and after antifungal therapy - Venturini, James [UNESP]; Cavalcante, Ricardo Souza [UNESP]; Sylvestre, Tatiane Fernanda [UNESP]; Santos, Rodolfo Ferreira dos [UNESP]; Moris, Daniela Vanessa [UNESP]; Carvalho, Lidia Raquel [UNESP]; Parreira de Arruda, Maria Sueli [UNESP]; Golim, Marjorie de Assis [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Fundaco Oswaldo Cruz, 2017)
BACKGROUND The main clinical forms of paracoccidioidomycosis (PCM) are the acute/subacute form (AF) and the chronic form (CF), and they both display considerable clinical variability. The immune responses of PCM patients, during and after treatment, remain neglected, mainly in the case of CF patients, due to the high prevalence of pulmonary sequelae. OBJECTIVE To evaluate the distribution of whole blood T cell subsets, serum cytokines, and biomarkers of pulmonary fibrosis in PCM patients, according to the clinical form and at different time points, during the antifungal therapy. METHODS Eighty-seven PCM patients, from an endemic area in Brazil, were categorised into groups, according to the clinical form (AF or CF) and the moment of treatment. The peripheral blood T lymphocyte subsets of these patients were analysed using fluorescence-activated cell sorting. The serum levels of cytokines, basic fibroblast growth factor and surfactant protein-D (SP-D) were also analysed. FINDINGS In the CF patients, an expansion of the peripheral blood TCD4(+) cells was observed during the treatment, and this persisted even after two years of antifungal treatment. In addition, these patients showed high serum levels of SP-D. CONCLUSION Our findings highlight the immunological changes CF patients undergo, during and after treatment, possibly due to the hypoxia triggered by pulmonary fibrosis and emphysema.
Keywords: paracoccidioidomycosis; T-lymphocyte subsets; antifungal agents; pulmonary fibrosis; emphysema; surfactant protein-D